Efficacy of Levocetirizine & cetirizine in Chronic Idiopathic Urticaria in Pakistani Population. - Abdul Sattar Khoso, Ghtilam Rasool Mashori (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2013)
Objective: Comparative trial of levocetrizine and cetirizine in chronic idiopathic urticaric patients in Pakistani population. Design: Randomized, clinical trial. Setting: Department of Pharmacology B.M.S.I, OPD of Dermatology, JPMC, Karachi Duration: June 2008 to December 2008. Methods: Patients were randomized into two groups A (n=40) and B (n=40). Patients registered in each group were 15-60 years of age. Group A patients were treated with levocetirizine 5mg once daily. Group B patients were administered cetirizine 10mg. The study design was approved by ethical committee of the institution. Results: Levocetirizine 5mg was more effective as compared to cetirizine in 90 days treatment period. The results are shown from baseline to day-90. Levocetirizine in group A reduced the itching from 2.07±0.10 to 0.17±0.06, intensity of erythema from 2.20±0.06 to 0.27±0.07, number of hives from 1.8±0.09 to 0.3±0.07, size of largest hive from 0.82±0.12 to0.17±0.06, and extent of skin involvement from 1.85±.09 to 0.17±.06. Whereas Cetirizine in B group reduced itching from 2.22±0.08 to 0.42±0.07, intensity of erythema from 1.82±0.09 to 0.35±0.07, number of hives from 1.97±0.08 to 0.22±0.06, size of largest hive from 0.72±0.10 to0.20±0.06 and extent of skin involvement from 2.10±.07 to 0.32±.0.07 at day 90. There were less adverse effects oflevocetirizine than cetirizine. Conclusion: The study demonstrate that levocetrizine 5 mg was more effective as compared to cetirizine 10 mg in reducing the symptoms of chronic idiopathic urticaria; so levocetirizine was more potent as compared to cetirizine.